Impact of Blessing Energy Treatment on the Morphological Development and Yield Performance of Green Zucchini (Cucurbita pepo L.) - Jana, Snehasis; Branton, Alice; Phutankar, Nikhil Rajendra; Gaikwad, Tejas Bapu; Kadam, Vivek Dattaram; Mondal, Sambhu (European Journal of Applied Sciences, 2026)
Background: As the demand for sustainable agricultural practices increases, non-invasive complementary and alternative techniques are being explored to enhance crop productivity without chemical intervention. This study investigated the impact of exogenous spiritual blessing energy treatment (SBET) on the growth dynamics and reproductive output of Green Zucchini (Cucurbita pepo L.). Method: An open-field experimental study was conducted to evaluate the effects of SBET on zucchini plants growth, morphology, and productivity. Seeds and plot were subjected to specific SBET from a distance for a duration of 4 minutes in a single exposure. Growth parameters, including plant height, leaf area, and stem diameter, etc. were measured throughout the farming period. Yield performance was assessed based on the number of fruits per plant, average fruit weight, and total marketable yield at harvesting. Results: Most of qualitative morphological traits were positively remarkably altered in the treatment group compared to the control. Different phenological traits such as plant height, number of nodes per plant, and leaf width were increased by 34.10% (p = 0.001), 101.08% (p ≤ 0.001), and 33.81% (p = 0.001), respectively, compared to the control. Moreover, fruit length, seed width, and seed count per fruit were significantly increased by 33.53% (p ≤ 0.001), 44.68% (p = 0.004), and 37.02% (p ≤ 0.001), respectively, compared to the control. Furthermore, at the end of harvesting total fruit yield (tons per hectare) were improved by 25.36% in the treatment group compared to the control. Conclusion: The application of exogenous SBET (Trivedi Effect®) serves as a potent physical priming agent that positively modulates the physiological and morphological development of Cucurbita pepo L.